Back to normal? A retrospective study on stimulation test and endocrinological diagnosis before, during and after COVID-19 pandemics - Peinkhofer, Martina; Passarella, Sofia; Dalena, Paolo; Tamaro, Gianluca; Vidonis, Viviana; Vittori, Giada; Slama, Daniela; Faleschini, Elena; Barbi, Egidio; Tornese, Gianluca (Frontiers in Endocrinology, 2025)
IntroductionThe COVID-19 pandemic disrupted healthcare systems, affecting consultations and diagnostics. In pediatric endocrinology, referral patterns shifted, with increased central precocious puberty (CPP) diagnoses and decreased growth hormone deficiency (GHD) evaluations. This study examines trends in stimulation tests, referrals, and diagnoses from 2019 to 2023 to assess the pandemic’s impact on pediatric endocrinology.MethodsThis retrospective study analyzed stimulation tests performed at the Institute for Maternal and Child Health IRCCS “Burlo Garofolo,” Trieste, Italy, from 2019 to 2023, divided into pre-pandemic (2019–March 2020), pandemic (March 2020–January 2022), and post-pandemic (February 2022–December 2023) phases.ResultsA total of 1,526 tests were conducted on 1,042 patients. Tests per day remained stable (pre-pandemic: 0.84; pandemic: 0.82; post-pandemic: 0.85). The Arginine Stimulation Test (ATT), the most frequent test pre-pandemic (31%), decreased during the pandemic (20%, p<0.001), while the LHRH Test (LHRHT) increased from 22% to 28% (p<0.001), becoming the most requested test. Diagnosis rates for GHD and CPP remained stable, but the proportion of females diagnosed with CPP increased significantly during the pandemic (91% vs. 69%, p=0.022). CPP testing declined (p=0.018) post-pandemic, while GHD testing returned to pre-pandemic levels.ConclusionThe pandemic altered diagnostic patterns, with reduced GHD evaluations reflecting limited healthcare access. Post-pandemic recovery suggests a resolution of diagnostic delays. The temporary surge in CPP cases, likely influenced by pandemic-related lifestyle changes, subsided post-pandemic, aligning with pre-pandemic trends. To date, no other studies have reported similar variations in GHD incidence during the pandemic.